2009
DOI: 10.1017/s1049023x00007238
|View full text |Cite
|
Sign up to set email alerts
|

Protection Against Cold in Prehospital Care—Thermal Insulation Properties of Blankets and Rescue Bags in Different Wind Conditions

Abstract: In a cold, wet, or windy environment, cold exposure can be considerable for an injured or ill person. The subsequent autonomous stress response initially will increase circulatory and respiratory demands, and as body core temperature declines, the patient's condition might deteriorate. Therefore, the application of adequate insulation to reduce cold exposure and prevent body core cooling is an important part of prehospital primary care, but recommendations for what should be used in the field mostly depend on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
0
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 19 publications
2
54
0
4
Order By: Relevance
“…It has been shown that a moderate wind speed (3 m/s) decreases the thermal insulation of low insulation covers by 20% to 40%, and that of high insulation covers by 15% to 25%. 9 It has been shown that high wind speeds (12 m/s to 18 m/s) will decrease the thermal insulation of highly impermeable clothing ensembles by 30% to 40%. The decrease of the thermal insulation in wind is caused mostly because of boundary layer breakdown and compression effects.…”
Section: Evaluation and Comparison Of Protective Coveringsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that a moderate wind speed (3 m/s) decreases the thermal insulation of low insulation covers by 20% to 40%, and that of high insulation covers by 15% to 25%. 9 It has been shown that high wind speeds (12 m/s to 18 m/s) will decrease the thermal insulation of highly impermeable clothing ensembles by 30% to 40%. The decrease of the thermal insulation in wind is caused mostly because of boundary layer breakdown and compression effects.…”
Section: Evaluation and Comparison Of Protective Coveringsmentioning
confidence: 99%
“…These results correspond with the literature. 9 Wet garments inside the coverings increased evaporative heat transfer from the skin. Therefore, the dry thermal resistance of the coverings declined.…”
Section: Evaluation and Comparison Of Protective Coveringsmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, evaporative heat loss may be minimised by adding an airtight vapour barrier immediately outside the wet clothing 52. Recent studies have suggested that the optimal packaging method for wet conditions is a combination of a vapour-tight inner layer followed by a dry insulating middle layer covered in a wind-resistant and water-resistant outer wrapping 53 54. Obtaining vascular access may be difficult due to hypothermic and/or hypovolaemic vasoconstriction.…”
Section: Resultsmentioning
confidence: 99%
“…Recent research investigating rescue blankets using a supine thermal manikin, dressed in thin underwear, identified that materials with a metallic coating had higher thermal resistance than would be expected from their thickness [4]. For example, a 0.01-mm thick dual surface (gold/silver) metallic laminated plastic foil blanket had the same thermal resistance as a 5.5-mm thick felted wool blanket (2.9 AE 0.1 Clo and 2.7 AE 0.1 Clo, respectively).…”
Section: Introductionmentioning
confidence: 99%